Predictors of patent and occlusive hemostasis after transradial coronary procedures. Issue 7 (17th June 2020) - Pacchioni, Andrea; Bellamoli, Michele; Mugnolo, Antonio; Ferro, Jayme; Pesarini, Gabriele; Turri, Riccardo; Ribichini, Flavio; Saccà, Salvatore; Versaci, Francesco; Reimers, Bernhard
Abstract: Objectives: To assess the independent predictors of patent and occlusive hemostasis (PH and OH, respectively) during radial hemostasis after coronary procedures. Background: Radial artery occlusion (RAO) is a thrombotic complication of transradial catheterization that can lead to permanent occlusion of the radial artery. Sheath‐vessel diameter ratio, postprocedure compression time, occlusive hemostasis, inadequate, and excessive anticoagulation are all predictors of RAO. Methods: As a part of a previously published study investigating the relationship between residual anticoagulation and risk of RAO, 837 patients undergoing transradial diagnostic coronary angiography or percutaneous coronary interventions were enrolled. Cumulative heparin dose used during the procedure and ACT measured before sheath removal were recorded. PH with reverse Barbeau test was attempted in all patients (NCT02762344). Results: PH was less frequently obtained for increasing cumulative heparin dose and ACT values ( p  < .0001 and p  = .0034, respectively). At logistic regression analysis both cumulative heparin dose and ACT values were independent predictors of OH (OR 1.017, 95% IC 1.011–1.023 p  < .0001 and OR 1.004, 95% IC 1.001–1.006, p  = .0004) while adjusted probability for RAO showed exponential relationship with both parameters. Conclusions: The level of anticoagulation is strongly related to the incidence of RAO, and should be taken into account when choosing hemostasis protocol.